2017
DOI: 10.1158/1078-0432.ccr-16-2632
|View full text |Cite
|
Sign up to set email alerts
|

Selinexor (KPT-330) Induces Tumor Suppression through Nuclear Sequestration of IκB and Downregulation of Survivin

Abstract: Purpose: Selinexor, a small molecule that inhibits nuclear export protein XPO1, has demonstrated efficacy in solid tumors and hematologic malignancies with the evidence of clinical activity in sarcoma as a single agent. Treatment options available are very few, and hence the need to identify novel targets and strategic therapies is of utmost importance.Experimental Design: The mechanistic effects of selinexor in sarcomas as a monotherapy and in combination with proteasome inhibitor, carfilzomib, across a panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 40 publications
3
40
0
Order By: Relevance
“…Consistent with previous studies of KPT-330 on acute myeloid leukemia, our studies of KPT-330 in NHL showed induction of G1 cell cycle arrest in MCL and TCL 9 . As was shown in sarcoma and MCL in previous studies, we also found that MCL cells have increased IkB localization in the nucleus with KPT-330 treatment 10,11 . In recent studies, it was found that bortezomib and DNA damaging agents such as gemcitabine impose a synergistic antitumor effect when combined with KPT-330 in solid tumors such as sarcoma and breast cancer, and hematologic malignancies such as AML, MM, and DLBCL [4][5][6]8,12 .…”
supporting
confidence: 89%
“…Consistent with previous studies of KPT-330 on acute myeloid leukemia, our studies of KPT-330 in NHL showed induction of G1 cell cycle arrest in MCL and TCL 9 . As was shown in sarcoma and MCL in previous studies, we also found that MCL cells have increased IkB localization in the nucleus with KPT-330 treatment 10,11 . In recent studies, it was found that bortezomib and DNA damaging agents such as gemcitabine impose a synergistic antitumor effect when combined with KPT-330 in solid tumors such as sarcoma and breast cancer, and hematologic malignancies such as AML, MM, and DLBCL [4][5][6]8,12 .…”
supporting
confidence: 89%
“…We also tested vincristine and cyclophosphamide because of their inclusion in an effective chemotherapy regimen for softtissue sarcomas [40]. The nuclear transporter XPO1 inhibitor KPT-330 was included in the candidate list because it showed antitumor activity against MPNSTs [41], KRASdriven lung cancer [42], and T-cell acute lymphoblastic leukemia harboring activating mutations of NRAS and NOTCH1 [43]. Finally, etoposide and topotecan were considered potentially useful drugs because of their activity in the treatment of advanced soft-tissue sarcomas, alone or in combination with other agents [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have provided a rationale for combining selinexor with PIs (Kashyap et al , ; Nair et al , ; Rosebeck et al , ; Turner et al , ). The addition of selinexor to a PI has a synergistic effect on cell death of myeloma cell lines and primary plasma cells derived from patients with RRMM, and the combination demonstrated greater antimyeloma activity in a murine xenograft model than either agent alone (Kashyap et al , ; Rosebeck et al , ; Turner et al , ).…”
mentioning
confidence: 99%